2019
DOI: 10.3390/polym11091424
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Electrospinning of Gelatin/Pullulan Composite Nanofibers

Abstract: In this study, gelatin and pullulan were successfully prepared as a novel type of protein–polysaccharide composite nanofibrous membrane by electrospinning at room temperature with deionized water as the solvent. The effects of gelatin content on the properties of the solution, as well as the morphology of the resultant nanofibers, were investigated. Scanning electron microscopy (SEM) was utilized to observe the surface morphology. Fourier transform infrared spectroscopy (FTIR) was used to study the interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…The results suggested that the JFP can form intermolecular hydrogen bonding with pullulan and improve the tensile strength. The improvement of tensile strength will help JFP/pullulan nanofiber retain good mechanical properties during storage [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results suggested that the JFP can form intermolecular hydrogen bonding with pullulan and improve the tensile strength. The improvement of tensile strength will help JFP/pullulan nanofiber retain good mechanical properties during storage [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…This can be achieved by either adjusting the polymer solution concentrations or through the manufacturing process. This can be seen in a study by Wang et al, whereby nanofibers were formulated through electrospinning comprised on gelatin and pullulan (a microbial polysaccharide) for consideration as a tissue engineering scaffold [ 39 ]. In this study, the effect of a change in gelatin content on the properties of the solution and the resultant nanofibers was investigated.…”
Section: Biofabrication Strategies For Tissue Engineeringmentioning
confidence: 99%
“…Wang and Ziegler [71] prepared electrospun nanofiber mats from aqueous starch-pullulan dispersions. Moreover, Wang et al [72,73] prepared electrospun gelatin/PUL fibers mimicking ECM. Hence, PUL was electrospun in combination with specific polymer, nanofillers, or compounds for obtaining functional nanostructured mats.…”
Section: Pullulan and Extra Cellular Matrixmentioning
confidence: 99%